Lower Respiratory Tract Infection in a Renal Transplant Recipient: Do not Forget Metapneumovirus - N. Noel; B. Rammaert; J. Zuber; N. Sayre; M. F. Mamzer-Bruneel; M. Leruez-Ville; L. Mascard; M. Lecuit; O. Lortholary (Case Reports in Transplantation)
Human metapneumovirus (hMPV) is emerging as a cause of a severe respiratory tract infection in immunocompromised patients. hMPV pneumonia has only been seldom reported in nonpulmonary solid organ transplanted patients, such as renal transplant recipients. We report here a case of a 39-year-old patient presenting with fever, cough, and interstitial opacities on CT scan diagnosed as a nonsevere hMPV pneumonia 11 years after a renal transplantation. Infection resolved spontaneously. Differential diagnosis with Pneumocystis pneumonia was discussed. We review the medical literature and discuss clinical presentation and detection methods that can be proposed in solid organ transplant recipients.